Uptake of pharmaceuticals acts as an abiotic stress and triggers variation of jasmonates in Malabar spinach (Basella alba. L). (December 2019) - Zhang, Tianlang; Qiu, Junlang; Chen, Guosheng; Xu, Jianqiao; Zhu, Fang; Ouyang, Gangfeng
Abstract: In recent years, pharmaceuticals have received increasing attentions because of their potential risks to the environment, but researches focusing on their impacts on defense system of living plants are still lacking. As an important class of phytohormones, jasmonates play crucial roles in plant defense system against environmental stress. In order to investigate the effect of pharmaceuticals uptake on endogenous jasmonates, an in vivo solid phase microextraction (SPME) method was established to simultaneously detect and monitor both pharmaceuticals and jasmonates in living plants. The proposed method exhibited wide linear ranges, high sensitivity (limits of detection ranging 0.0043–0.035 ng g −1 for pharmaceuticals and 0.091–0.22 ng g −1 for jasmonates, respectively), and satisfactory reproducibility (relative standard deviation of intrafiber ranging 4.2%–8.6% and interfiber ranging 5.2%–8.2%, respectively). Subsequently, this method was successfully applied to track the concentrations of each pharmaceutical and corresponding jasmonates in living Malabar spinach plants ( Basella alba. L ) exposed to three common pharmaceuticals (i.e. gemfibrozil, mefenamic acid and tolfenamic acid) over 15 days. In result, all pharmaceuticals appeared to trigger intensive biosynthesis of jasmonic acid (JA) (3.1–9.4 times of control) while reduced the concentration of methyl jasmonate (MeJA) (18.3%–38.1% of control). We inferred that uptake of pharmaceuticals acted as an abiotic stress and stimulated the plant defense response because of the variation of jasmonates. To the best of our knowledge, this is the first study applying SPME to detect and track both pharmaceuticals and phytohormones in living plants, which not only provided a glimpse to the adverse effect of pharmaceuticals on plants as well as the regulation of endogenous jasmonates, but also set a promising template for future in vivo analysis of xenobiotics and plant endogenous substances. Graphical abstract: Image 1 Highlights: In vivo solid phase microextraction was developed to detect pharmaceuticals and jasmonates simultaneously in living plants. In vivo monitoring of jasmonates in malabar spinach exposed to pharmaceuticals was realized. Uptake of pharmaceuticals triggered variations of jasmonates and stimulated plant defense response. Understanding of the physiological effects of pharmaceuticals uptake on endogenous phytohormones regulation was supplemented.